PERENCANAAN KEUANGAN SYARIAH BAGI KELUARGA PADA DESA CIASMARA, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR - Kusumaningrum, Ria; Melinasari, Susi; Putri, Wulan Purnama (Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah: Program Studi Perbankan Syariah., 2024)
Sharia financial planning is an important aspect in Muslim family life. This research aims to analyze sharia financial planning for families in Ciasmara Village so they can manage their finances in accordance with sharia principles. The subjects of this research were families in Ciasmara Village. This research uses ABCD methods. The research results show that the sharia financial planning implemented by families in Ciasmara Village is still not optimal. This is caused by several factors, namely lack of knowledge about Islamic finance, limited access to information, and consumer culture.